Rancang Bangun Alat Ukur Tribometer Pin-On-Disc Dengan Penggerak Motor Dc Gearbox 12 Volt - Moh Erwin Baharuddin; Slamet Supriyadi; Aan Burhanudin (Universitas Muhammadiyah Yogyakarta, 2022)
Tribometer is a tool to determine the occurrence of surface contact wear. The purpose of this research is to design a pin-on-disc tribometer. The design stage involves making a mechanical design, a series of sensors, and designing a complete tool. Tribometer input and output electrical sensor circuit. The software used to program the tribometer is Arduino and uses C++ programming. The pin on disc test stages includes weighing the disc and load variations and setting the disc rotation as desired.